Does Digital Technology Boost Intention to Pay Zakat? Integration of UTAUT 2 and Initial Trust - M Jaenudin; Yan Putra Timur; Abdul Basit; Ririn Tri Ratnasari; Ririt Iriani Sri Setiawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Digital technology is key to increasing donor intentions to contribute to Zakat, Infaq, and Sadaqah (ZIS).Â This study identified the factors influencing and dominating donors in making digital payments for ZIS. Combining UTAUT 2 and the initial trust model, this study analyzed data from an online survey involving 103 donors from various provinces in Indonesia. The study includes donors who have paid or intend to pay the ZIS digitally. The results of the analysis using the partial least squares structural equation model (PLS-SEM) indicated that performance expectancy had no significant effect on initial trust and behavioral intention. Likewise, facilitating conditions did not significantly affect initial trust. On the other hand, hedonic motivation positively and significantly affects initial trust and behavioral intention, while initial trust affects behavioral intention. This study suggests that zakat institutions must ensure that their systems offer user satisfaction, initial trust, and facilitating conditions, such as reliable networks and security.